Probing the intergalactic medium with Lyα and 21 cm fluctuations - Heneka, Caroline; Cooray, Asantha; Feng, Chang (The astrophysical journal, 2017)
We study 21 cm and Ly α fluctuations, as well as H α , while distinguishing between Ly α emission of galactic, diffuse, and scattered intergalactic medium (IGM) origin. Cross-correlation information about the state of the IGM is obtained, testing neutral versus ionized medium cases with different tracers in a seminumerical simulation setup. In order to pave the way toward constraints on reionization history and modeling beyond power spectrum information, we explore parameter dependencies of the cross-power signal between 21 cm and Ly α , which displays a characteristic morphology and a turnover from negative to positive correlation at scales of a couple Mpc −1 . In a proof of concept for the extraction of further information on the state of the IGM using different tracers, we demonstrate the use of the 21 cm and H α cross-correlation signal to determine the relative strength of galactic and IGM emission in Ly α . We conclude by showing the detectability of the 21 cm and Ly α cross-correlation signal over more than one decade in scale at high signal-to-noise ratio for upcoming probes like SKA and the proposed all-sky intensity mapping satellites SPHEREx and CDIM, while also including the Ly α damping tail and 21 cm foreground avoidance in the modeling.
Gesehen am 01.09.2020